2005
DOI: 10.1103/physrevlett.95.017201
|View full text |Cite|
|
Sign up to set email alerts
|

High Temperature Ferromagnetism in GaAs-Based Heterostructures with MnδDoping

Abstract: We show that suitably designed magnetic semiconductor heterostructures consisting of Mn delta (delta)-doped GaAs and p-type AlGaAs layers, in which the locally high concentration of magnetic moments of Mn atoms are controllably overlapped with the two-dimensional hole gas wave function, realized remarkably high ferromagnetic transition temperatures (T(C)). A significant reduction of compensative Mn interstitials by varying the growth sequence of the structures followed by low-temperature annealing led to high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(53 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…According to the delta function-like doping profile, the Mn atoms are expected to substitute for all Ga sites in a single layer, which can exhibit high transition temperatures close to room temperature due to local high dopant and carrier concentration (Nazmul et al, 2005). Recent theoretical considerations show that ferromagnetism can be stabilized in such a single layer of magnetic ions (Melko et al, 2007), although the Mermin-Wagner theorem implies that in the absence of magnetic anisotropy gapless spin excitations always destroy the ferromagnetic order in two dimensions.…”
Section: C4 Ferromagnetic Spin-rtdsmentioning
confidence: 99%
“…According to the delta function-like doping profile, the Mn atoms are expected to substitute for all Ga sites in a single layer, which can exhibit high transition temperatures close to room temperature due to local high dopant and carrier concentration (Nazmul et al, 2005). Recent theoretical considerations show that ferromagnetism can be stabilized in such a single layer of magnetic ions (Melko et al, 2007), although the Mermin-Wagner theorem implies that in the absence of magnetic anisotropy gapless spin excitations always destroy the ferromagnetic order in two dimensions.…”
Section: C4 Ferromagnetic Spin-rtdsmentioning
confidence: 99%
“…On one hand, these δ-doped structures allow a concentration of Mn higher than in random-doped (Mn) III-V semiconductors, and thus, due to the different valence between the group III atom and the substitutional Mn, can produce in principle a larger concentration of holes, enhancing the Curie temperature (T C ) of the system. On the other hand, DMS T C can increase considerably also because it depends on the spatial distribution of magnetic ions, which can change substantially in low-dimensional systems: Nazmul and co-workers [2] showed that in a p-type selectively doped III-V heterostructured composed of Mn δ-doped GaAs/p-AlGaAs a remarkably high T C of about 250 K can be reached; in Ref. [3] Chen et al report T C well above room temperature in GaSb/Mn digital alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Picosecond spin dynamics of photoinduced (nonequilibrium) spin polarization is also of major interest in ferromagnetic semiconductors of the type Ga 1−x Mn x As, which have recently been shown to reach Curie temperatures up to T C ≈ 250 K in suitable heterostructures (Nazmul et al, 2005). This technique is believed to contribute to the development of ultrafast magnetic devices in spintronics.…”
Section: Magneto-optical Semiconductorsmentioning
confidence: 99%